Economic Integration and Monetary Union - Andrew Coleman (New Zealand Government, The Treasury, 1999)
Recent research shows that trade of goods and financial products is much greater within countries than it is between countries, even allowing for factors such as transports costs. This lack of economic integration is likely to be costly for small nations, as internal trade is much less diverse than internal trade in large nations. European countries have long argued that the adoption of a single currency is a primary means to enhance economic and social integration, and with the adoption of the euro most European countries have given up monetary independence in order to gain these benefits. This paper examines the modern literature analysing the costs and benefits of forming a monetary union. It contends that New Zealand should reassess the merits of these arguments, although it does not perform a cost benefit analysis for New Zealand, or even recommend whose currency should be preferred. It appears that the benefits of monetary independence are lower than previously thought. This is because most countries have attained low inflation, and because of new evidence that the volatility of exchange rates inherent with monetary independence may be the cause of economic shocks rather than the means of adjusting to economic shocks.
Keywords: 330